Output gaps in European Monetary Union: New insights from input augmentation in the technological progress - Maria Antoinette Dimitz (Institute for Advanced Studies (IHS), 2001)
Output gaps for ten European countries and the USA are estimated based on a CES production function with input augmentation in the technological progress. The substitution parameter is estimated from the coefficients of the labor and capital demand functions. The estimation is done using Johansen's cointegration method. For six of the eleven countries analyzed, the use of the Cobb Douglas form would not be appropriate. The output gaps show a similar cyclical pattern for all countries. They remain mostly within ±3% for five countries and within ±5% for another four. Separating labor- and capital-augmenting technological progress gives insight into the driving forces of growth.
Keywords: C32; E32; 330; output gap; potential output; CES production function; EMU; Gesamtwirtschaftliche Produktion; Wirtschaftspotenzial; CES-Produktionsfunktion; Europäische Wirtschafts- und Währungsunion; EU-Staaten